Investigation Of an Epidemic of Hepatitis in Ahmedabad City - Sheetal Vyas; Sonal Parikh; Rachna Kapoor; Vaibhavi Patel; Anand Solanki (Medsci Publications, 2010)
This study explores geographic distribution, clinical profile of Hepatitis cases and confirms the strain serologically. The investigation was conducted by the rapid response team of the Smt. NHL Municipal Medical College in the Hirawadi area of North Zone of Ahmedabad following reporting increased numbers and clustering of jaundice cases during routine survey by the link and health workers of Ahmedabad Municipal Corporation. Re-survey of the affected area was carried out and occurrence of new cases in the areas was noted along with collection of blood samples. Assessment of water distribution system and correction of faults was carried out simultaneously by the engineering department of AMC. A total of 377 houses were surveyed and it had total population of 2039. Total jaundice cases reported were 94. Age profile was assessed among the population of 1245 and the age cut-off was taken as 12 years so as to make epidemiological distinction between two types of water borne Hepatitis based on the survey data before the reports of laboratory are available. Sex wise distribution of population and cases showed male preponderance. Overall ratio of jaundice cases among <12 years versus >12 years age category was 1:15.25. Households having turbid water supply had significantly a greater number of cases. Overall attack rate was 5.22% with significantly higher attack rate in population over 12 years. Total 44 blood samples were taken and 33 (75%) of samples were positive for Hepatitis E whereas 5 (11%) samples were positive for both hepatitis A and E. HEV was confirmed as the major etiological agent in this outbreak and contaminated drinking water was identified as the source of infection.